Identification and characterization of spontaneous AA amyloidosis in CD-1 mice used in toxicity studies: implications of SAA1 and SAA2 copy number variations - Mizukawa, Mao; Tanaka, Kohei; Kashimura, Akane; Uchida, Yu; Shiga, Takanori; Aihara, Naoyuki; Kamiie, Junichi (Journal of Toxicologic Pathology, 2025)
Amyloidosis is characterized by the extracellular deposition of insoluble protein fibrils that cause cellular damage and dysfunction in organs and tissues. Multiple types of amyloidosis and their causative precursor proteins have been identified in humans and animals. In toxicological studies, a high incidence of spontaneous amyloidosis has been reported in CD-1 mice; however, the precursor protein responsible remains unclear. In contrast, B6C3F1 mice have a low incidence of amyloidosis. This study aimed to identify the types of amyloidosis and causative precursor proteins in CD-1 mice and investigate the role of copy number variations (CNVs) in genes encoding precursor proteins in different mouse species. Histopathological examination revealed amyloids in multiple organs, which were confirmed by direct fast scarlet staining. Immunohistochemistry and liquid chromatography-tandem mass spectrometry analyses revealed that the deposition was derived from serum amyloid A (SAA1 and 2), suggesting that the CD-1 mice had AA amyloidosis. Copy number variation assays demonstrated higher copy numbers of SAA1 and SAA2 in CD-1 mice with amyloidosis than in C3H/He mice (the parent strain of B6C3F1 mice). These findings suggest that the high copy numbers of SAA1 and SAA2 may contribute to the high incidence of AA amyloidosis in CD-1 mice. This study examined spontaneous amyloidosis in CD-1 mice and revealed the correlation between SAA1 and SAA2 CNVs in the pathogenesis of the disease and the genetic factors influencing amyloidosis in mice.